2010
DOI: 10.1097/mej.0b013e32832dd8ee
|View full text |Cite
|
Sign up to set email alerts
|

Takotsubo cardiomyopathy associated with diving

Abstract: Takotsubo cardiomyopathy consists of cardiomyopathy with transient apical ballooning and left ventricular systolic dysfunction in the absence of atheromatous disease of the coronary arteries, accompanied by ECG changes together with elevated cardiac enzymes appearing in a context of emotional or physical stress. A 51-year-old woman was referred to our emergency department for treatment after chest pain associated with acute dyspnoea during diving. On questioning, the patient confirmed that she had twice dived … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 5 publications
1
13
0
Order By: Relevance
“…We performed a literature search through PubMed and Medline of all available English language articles pertaining to stress cardiomyopathy and diving. We came across only 2 articles addressing this issue (4,9). Chenaitia et al reported a case of Takotsubo cardiomyopathy in a 51-year-old woman after diving to a depth of 35 meters.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…We performed a literature search through PubMed and Medline of all available English language articles pertaining to stress cardiomyopathy and diving. We came across only 2 articles addressing this issue (4,9). Chenaitia et al reported a case of Takotsubo cardiomyopathy in a 51-year-old woman after diving to a depth of 35 meters.…”
Section: Discussionmentioning
confidence: 95%
“…Less commonly, there may be hypokinesis of the mid-ventricle or hypokinesis of the base with sparing of the mid-ventricle and apex, also referred to as inverse or reverse Takotsubo (3). There have been few reported cases of Takotsubo cardiomyopathy associated with diving (4,5). We describe a case of stress cardiomyopathy caused by diving and review the available literature on this subject.…”
Section: Introductionmentioning
confidence: 98%
“…Two cases were excluded, the first was a 79-year-old woman who developed TC after a swimming accident where the patient was dragged by the stream but immediately rescued by lifeguards without drowning [5], and the second case was a 51-year-old woman who developed TC from a diving accident after she had dived twice to 35 m without any decompression stops [6]. The remaining 8 cases of near drowning [4,[7][8][9][10][11][12][13] had a mean age of 53 years, and 75% were males.…”
Section: Resultsmentioning
confidence: 99%
“…(These latter diagnoses were not included in Table 1.) Of the 50 IPE cases found to have evidence of cardiac dysfunction, valvular disease was found in 6 cases (6,29,34) and LV dysfunction was found in 26 cases (5,11,14,20,27,35,60) ( Table 2). The mean age of those with risk factors for coronary artery disease (hypertension, hypercholesterolemia, or smoking history) was 53.0 T 6.8 yr versus 45.7 T 12.0 yr in those without risk factors (P = 0.0001).…”
Section: Resultsmentioning
confidence: 99%